The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1108/ijlma-10-2017-0253
|View full text |Cite
|
Sign up to set email alerts
|

A study of whistle-blowing intentions of teachers working in higher education sector

Abstract: Purpose This paper aims to explore the key factors which influence whistleblowing intentions of teachers working with higher education institutions (HEIs) in India. Both internal and external whistleblowing intentions of the HEI teachers are studied by examining their relative intentions to report a potential wrongdoing to the authorities within the management of the institution and to the external statutory bodies. The reporting intentions of the HEI teachers are measured through the use of three vignettes re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 71 publications
(65 reference statements)
0
14
0
1
Order By: Relevance
“…One study reported that aversive leaders elicited greater whistle-blowing intentions in financially unstable organizations (Thoroughgood et al, 2011). Communication between workers and management was examined across five studies and communication quality with management was positively associated with whistleblowing intentions in all of these studies (Richardson et al, 2008;Zhang, 2008;Lyndon et al, 2012;Kamarunzaman et al, 2014;Chaudhary et al, 2019). In terms of leadership style, transformational leadership (Caillier, 2013), laissez-faire style (Erturk and Donmez, 2016), and an authentic style (Liu et al, 2015) were positively associated with whistleblowing intentions.…”
Section: Leadershipmentioning
confidence: 99%
See 1 more Smart Citation
“…One study reported that aversive leaders elicited greater whistle-blowing intentions in financially unstable organizations (Thoroughgood et al, 2011). Communication between workers and management was examined across five studies and communication quality with management was positively associated with whistleblowing intentions in all of these studies (Richardson et al, 2008;Zhang, 2008;Lyndon et al, 2012;Kamarunzaman et al, 2014;Chaudhary et al, 2019). In terms of leadership style, transformational leadership (Caillier, 2013), laissez-faire style (Erturk and Donmez, 2016), and an authentic style (Liu et al, 2015) were positively associated with whistleblowing intentions.…”
Section: Leadershipmentioning
confidence: 99%
“…Fifteen studies (Schultz et al, 1993;Kaplan and Whitecotton, 2001;Ayers and Kaplan, 2005;Curtis, 2006;Kaplan et al, 2009a,b;Kennett et al, 2011;Cho and Song, 2015;Gao et al, 2015;Alleyne et al, 2017Alleyne et al, , 2018Alleyne et al, , 2019Latan et al, 2018;Chaudhary et al, 2019) reported that personal costs such as monetary or job loss were negatively associated with whistleblowing intentions. Interestingly, Oelrich (2019) found that whistleblowing intentions were more strongly decreased by monetary losses than increased by monetary gains.…”
Section: Personal Costsmentioning
confidence: 99%
“…That applies either to academic and corporate settings. In regards to the academic environment, it must be embedded in a climate that truly supports ethical behavior by its members (Chaudhary, Gupta, & Phoolka, 2019). Higher ranking members (professors, directors, head of departments, etc.)…”
Section: Discussion and Theoretical And Practical Implicationsmentioning
confidence: 99%
“…Keempat yakni tindak lanjut di mana pelanggaran yang terlapor kan kemudian ditindaklanjuti untuk me nentukan tindakan yang diperlukan dalam menyelidiki suatu pelanggaran. Hal ini akan menunjukkan manfaat tindakan tersebut dan dapat mendorong untuk lebih aktif lagi melaporkan tindakan pelanggaran (Alleyne et al, 2017;Chaudhary et al, 2019).…”
Section: Metodeunclassified